Diagnosis and management of upper extremity deep-vein thrombosis in adults - Grant, Jonathan D; Stevens, Scott M; Woller, Scott C; Lee, Edward W; Kee, Stephen T; Liu, David M; Lohan, Derek G; Elliott, C Gregory (Thrombosis and haemostasis, 2012)
Upper extremity deep-vein thrombosis (UEDVT) is common and can cause important complications, including pulmonary embolism and post-thrombotic syndrome. An increase in the use of central venous catheters, particularly peripherally inserted central catheters has been associated with an increasing rate of disease. Accurate diagnosis is essential to guide management, but there are limitations to the available evidence for available diagnostic tests. Anticoagulation is the mainstay of therapy, but interventional treatments may be considered in select situations. The risk of UEDVT may be reduced by more careful selection of patients who receive central venous catheters and by use of smaller catheters. Herein we review the diagnosis, management and prevention of UEDVT. Due to paucity of research, some principles are drawn from studies of lower extremity DVT. We present a practical approach to diagnosing the patient with suspected deep-vein thrombosis of the upper extremity.